Orthopedics and trauma in children: key problems and future insights - Ghandour, Maher; Klotz, Matthias C. M.; Horsch, Axel (Children, 2023)
Orthopedic disorders among children are frequently encountered in clinical practice [...]
Gesehen am 09.03.2023